Inhibition of ABCG2 prevents phototoxicity in a mouse model of erythropoietic protoporphyria - Junjie Zhu; Fu-Ying Qin; Saifei Lei; Ruizhi Gu; Qian Qi; Jie Lu; Karl E. Anderson; Peter Wipf; Xiaochao Ma (Nature Communications)
Abstract Erythropoietic protoporphyria (EPP) is a genetic disease characterized by protoporphyrin IX-mediated painful phototoxicity. Currently, options for the management of EPP-associated phototoxicity are limited and no oral medication is available. Here, we investigated a novel therapy against EPP-associated phototoxicity by targeting the ATP-binding cassette subfamily G member 2 (ABCG2), the efflux transporter of protoporphyrin IX. Oral ABCG2 inhibitors were developed, and they successfully prevented EPP-associated phototoxicity in a genetically engineered EPP mouse model. Mechanistically, ABCG2 inhibitors suppress protoporphyrin IX release from erythroid cells and reduce the systemic exposure to protoporphyrin IX in EPP. In summary, our work establishes a novel strategy for EPP therapy by targeting ABCG2 and provides oral ABCG2 inhibitors that can effectively prevent protoporphyrin IX-mediated phototoxicity in mice.